Fabrication and characterization of AlGaAs/InGaAs-based pseudomorphic high electron mobility transistors (pHEMTs) - Lee, Hou Jang. (2009)
This work demonstrates the fabrication and operation of several types of pseudomorphic high electron mobility transistors (pHEMTs) and heterostructure field effect transistors (HFETs), which were our initial effort in gallium arsenide (GaAs) device fabrication. The aim of this work is to develop a repeatable fabrication process for heterostructure field effect transistors, especially pHEMTs, for future GaAs-based monolithic microwave integrated circuits (MMICs). The conventional, uniformly-doped AlxGa1-xAs/InyGa1-yAs pHEMT was the focus of investigation but a number of related but different pHEMT and HFET structures were fabricated for comparison. Based on the pseudomorphic AlxGa1-xAs/lnyGa1-yAs heterostructures, the following devices were fabricated and compared: (1) uniformly-doped pHEMT with x=0.2 (composition of Al), (2) planar layer-doped pHEMT with x=0.2, (3) planar layer-doped pHEMT with x=0.3, (4) delta-doped pHEMT with x=0.3, and (5) doped-channel HFET with x=0.3. All of these samples were grown by an in-house MBE system and processed within a class 100 clean room.